Characteristics of halal gelatin from red snapper (Lutjanus malabaricus) bone and its potency as beta-carotene coating material - Dwi Syanti Wirandhani; Mei Linda Nikma Nur Ulumi; Reza Fadilah Ardhani; Cathrine Olivia Andhani; Desiana Nuriza Putri (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Gelatin is a material produced from the partial hydrolysis of collagen sourced from the skin and bones of farm animals such as cows and pigs. Gelatin has been used for coatings because it has high permeability and dissolves in warm conditions, so the matrix cross-links are strong. The red snapper fillet processing industry produces 11.2-15% of waste, such as bone which has not been utilized optimally. The objective of this study was to determine the characterization of red snapper bone gelatin as a source of halal gelatin and measure its ability as a coating material for β-carotene pigment microencapsulation. Results showed the characteristics of red snapper bone gelatin with a yield of 10.71%, water content of 9.63%, protein content of 34.06%, ash content of 7.62%, gelatin fat content of 0.28%, and color intensity (L: 62.6). ; a+: 13.3 and b+: 30). The obtained halal gelatin was applied as a coating material for β-carotene pigment microencapsulation through the foam-mat method. It resulted in encapsulation with a yield of 16.75%, water content 9.25%, total carotenoid content 145.49 mg/g, surface carotenoid content 2.04%, solubility 78%, encapsulation efficiency 98.22%, color intensity (L: 50; a+: 29.9 and b+: 14.6), the particle size of 1004.04 μm and irregular shape.